2022
DOI: 10.4102/sajhrm.v20i0.1823
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human resource practices on employee retention: A study of three private higher educational institutions in the United Arab Emirates

Abstract: Orientation: Human resource (HR) practices have a significant impact on building the perceptions that define the relationships between employees and employers. Hence, it is imperative to develop further knowledge on how these HR practices impact employee retention within the higher education context.Research purpose: The purpose of this study was to examine the relationship between various HR practices and employee retention in an organisation. The article also investigates the effect of HR practices across em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…The theoretical implications of this study emphasize the importance of providing well‐designed training programs, setting clear expectations and formal job requirements, and creating a culture that values employee growth and development. Pharmaceutical organizations need to prioritize the development of their employees to enhance their job performance and retain skilled employees, reduce brain drain, and improve the quality of services offered (Alajlani & Yesufu, 2022). This can be achieved by providing systematic and well‐designed training programs that enhance employee skills, attitudes, and performance and also emphasize the need for organizations to allocate sufficient budget to analyze the specific needs of training and evaluate the results to ensure that training programs are effective in improving job performance of the pharmacists (Aman‐Ullah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical implications of this study emphasize the importance of providing well‐designed training programs, setting clear expectations and formal job requirements, and creating a culture that values employee growth and development. Pharmaceutical organizations need to prioritize the development of their employees to enhance their job performance and retain skilled employees, reduce brain drain, and improve the quality of services offered (Alajlani & Yesufu, 2022). This can be achieved by providing systematic and well‐designed training programs that enhance employee skills, attitudes, and performance and also emphasize the need for organizations to allocate sufficient budget to analyze the specific needs of training and evaluate the results to ensure that training programs are effective in improving job performance of the pharmacists (Aman‐Ullah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The essential objectives of organizational human resource management include recognizing employees as valuable assets and striving to maximize their contributions. This can be achieved through activities such as training and development (Alajlani & Yesufu, 2022) and compensation and rewards (Boselie et al, 2021; Reina & Scarozza, 2021), as highlighted by various studies (Alajlani & Yesufu, 2022; Aleem & Bowra, 2020; Reina & Scarozza, 2021). Numerous studies have extensively examined the impact of training and development on employee retention, making it one of the most studied human resource management practices (Akther & Tariq, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Folyamatos visszajelzés a teljesítményről (Alajlani & Yesufu 2022) Kérdőíves megkérdezés: alacsonyabb a kilépési szándéka azoknak a dolgozóknak, akik a formális teljesítményértékelés mellett folyamatos visszajelzést kapnak a teljesítményükről.…”
Section: Teljesítményértékelésunclassified
“…They emphasized the importance of selection methods. Another recent study by Alajlani & Yesufu [37] examined the relationship between HR practices and employee retention, as one of the performance dimensions, in higher education institutions in the UAE. They found that HR practices can improve employee retention.…”
Section: Figure 4 Relationship Between the Rp Es And Training Practic...mentioning
confidence: 99%